Intermetallic Phases in High-Entropy Alloys: Statistical Analysis of their Prevalence and Structural Inheritance - Ming-Hung Tsai; Ruei-Chi Tsai; Ting Chang; Wen-Fei Huang (Metals, 2019)
Strengthening high entropy alloys (HEAs) via second phases is a very effective approach. However, the design of intermetallic (IM) phases in HEAs is challenging, mainly because our understanding of IM phases in HEAs is still very limited. Here, a statistical approach is used to enhance our understanding towards IM phases in HEAs. A database consisting of 142 IM-containing HEAs was constructed. Our aim is twofold. The first is to reveal the most common IM phase types in published HEAs. The second is to understand whether HEAs inherit their IM structures from their binary/ternary subsystems, or whether they tend to form new structures irrelevant to their subsystems. The results show that the five most prevalent IM structures in the HEAs surveyed here are Laves, σ, B2, L12, and L21. This trend is evidently different from the overall trend among known binary/ternary IMs. As for structural inheritance, all the IM phases contained in the alloys are existing structures in the binary/ternary subsystems of the respective alloys. This suggests that the compositional complexity in HEAs does trigger additional complexity in IM structure formation. These findings have important implications in the future design and development of HEAs.